The mediating role of internal motivation on the relationship between ethical leadership and employee performance in hospitals in Northern Jordan - Raya Al-Bataineh; Ameera Hayajneh (PLoS ONE, 2026)
Objective The study’s main aim is to investigate the influence of ethical leadership (EL) on employee performance (EP) through internal motivation (IM) from the perspectives of clinical and administrative employees working in hospitals in northern Jordan. Method: Design The study used a descriptive, correlational cross-sectional quantitative design. Participants and setting Data were collected from 330 clinical and administrative employees between February and March 2024 using convenience sampling from five hospitals—2 public, 2 private, and 1 teaching hospital—in different geographical areas in northern Jordan. The study hypotheses were tested using a hierarchical multiple linear regression. Results The study results revealed a statistically significant association between ethical leadership, internal motivation, and employee performance. Moreover, the results showed that internal motivation statistically mediates the relationship between ethical leadership and employee performance. Conclusion The current study’s findings can serve as an empirical basis for hospital decision-makers to plan and implement programs and/or establish or revise policies for the target population, improving employees’ performance, achieving desired outcomes, and ultimately providing better care for patients.